Muscle Quality Index in Patients on Peritoneal Dialysis: Association with Clinical and Nutritional Factors - Maryanne Zilli Canedo Silva; Barbara Perez Vogt; Carla Maria Avesani; Fabiana Lourenço Costa; Pasqual Barretti; Jacqueline Costa Teixeira Caramori (Journal of Nephrology, 2026)
Abstract Background Patients on peritoneal dialysis (PD) are at risk of reduced muscle strength and mass. The clinical usefulness of muscle quality index (MQI), which integrates muscle quantity and function, remains unclear on PD. We evaluated the association between MQI, clinical, nutritional and physical function parameters on PD. Methods Study involving adult patients initiating PD. MQI was calculated as handgrip strength (HGS) divided by absolute appendicular muscle mass (AMM); where higher ratio indicates better muscle quality. Association analyses with MQI were performed with age, sex, albumin, bicarbonate, glycated hemoglobin (HbA1c), interleukin-6, leptin, C-reactive protein, body mass index, body fat percentage, protein equivalent of nitrogen appearance (PNA), phase angle, gait speed (GS), sit-to-stand, and Short Physical Performance Battery (SPPB). Results 47 patients (58±15 years; 50% male) were included. Absolute AMM was 20 ±6.5kg, HGS 22 [16-30] kg, and MQI 1.2±0.4 kgf/kg. MQI was significantly correlated with age (r=-0.550), HbA1c (r=-0.450), interleukin-6 (r=-0.415), GS (r=0.617), phase angle (r=0.647), SPPB (r=0.481), and PNA (g/day) (r=0.319). In linear regression models adjusted for age and sex, HbA1c (β=-0.383; 95% CI: -0.132- to -0.033, R2=0.414), phase angle (β=0.520; 95% CI: 0.90 to 0.304, R2=0.446), and GS (β=0.448; 95% CI: 0.174-1.048, R2=0.417) remained associated with MQI (p<0.01). Conclusions Patients initiating PD with higher age and HbA1c had lower MQI, while those with higher phase angle and GS had higher MQI. These results highlight the role of age, glycemic control, nutritional factors, and physical function in determining muscle quality, aggregating MQI as clinically useful in patients on PD.